The influence of the Palestinian Factionalsim and the political rifts on the political landscape and on the Palestinian Society in the West Bank and Gaza Strip - Bushkar, Amjad Husain Mohammad (Eximia, 2022)
The current empirical study aims to discuss the influence of the Palestinian factionalism on the political landscape in the West Bank and Gaza Strip. The study also seeks to identify the impact of the political rifts on the Palestinian factions, on the Palestinian people’s struggle against the occupying power, as well as on the structure of Palestinian society in all of its sectors. The study concluded that the occupation of Palestine since 1948 has been ushering the rise of political factionalism and rifts among the Palestinian people. Accordingly, this led to the formation of many Palestinian’s movements, factions, and forces operating outside the framework of the Palestine Liberation Organization, i.e., it transformed the Palestinian issue from a people's struggle for freedom and independence into a struggle for power. The findings of the current study further demonstrated that the Palestinian political factionalism and rifts led to the Palestinians’ disempowerment and preclude genuine mobilization. It also has a noticeable negative impact on the Palestinians’ social fabric, public services systems include the sectors of health, education, housing, the economic, etc. It also negatively influenced all the values, principles, customs and traditions that ruled the Palestinian society for years. Moreover, it allowed foreign countries to increase their interference in Palestinian affairs. Finally, the study demonstrated that the Palestinians’ political factionalism plays a major role in the occupation’s evasion of agreements and obligations under the pretext that there is no Palestinian partner for peace in light of the existence of two different political bodies who represent the Palestinian people. Furthermore, it led to increase the Palestinian youths’ immigration, the increase in suicide rates among the Palestinians youths of both males and females, partisans’ fanaticism, increase in the poverty rate and the lack of job opportunities, isolating the Gaza Strip from the West Bank, reducing the Palestinian society’s productive capabilities, decreasing its domestic and gross income rates, and at the top of that it created a state of partisans’ fanaticism among the Palestinians in Gaza Strip and the West Bank.